Enhancing Online Training in an Evidence-Based Treatment for Adolescent Panic Disorder: A Randomized Controlled Trial. Issue 4 (1st October 2016) - Ehrenreich-May, Jill; Dimeff, Linda A.; Woodcock, Eric A.; Queen, Alexander H.; Kelly, Tim; Contreras, Ignacio S.; Rash, Brian; Kelley-Brimer, Angela; Hauschildt, Jenny; Danner, Sankirtana Mundlapudi; Kennedy, Sarah M.; Barlow, David H.
ABSTRACT: This randomized controlled trial compared 3 modes of training clinicians in a youth-focused evidence-based treatment for panic disorder, using an additive design. Community practitioners ( N = 140) were randomly assigned to one of three conditions: a standard text-alone training condition (TXT); an interactive, online training program plus the TXT (TXT + OLT); or the TXT + OLT enhanced by a learning community adjunct leveraging Twitter (TXT + OLT + LC). Mastery of Anxiety and Panic for Adolescents (MAP-A), an efficacious cognitive-behavioral therapy for adolescents with panic disorder, was taught in all three training conditions. Analyses revealed that participants were more satisfied with the TXT + OLT and TXT + OLT + LC training, compared to the TXT condition. Although all conditions demonstrated equivalent increases in knowledge of MAP-A, participants in the TXT + OLT + LC demonstrated greater proficiency using MAP-A skills in a simulated clinical scenario, compared to those in both the TXT + OLT and TXT conditions. However, this effect was no longer statistically significant at a 90-day follow-up. Results indicate initial promise for enhancing online training dissemination efforts with a novel learning community and Twitter adjunct in training clinicians in a youth-focused, efficacious cognitive-behavioral therapy. Directions for future research and dissemination efforts are discussed.